2014
DOI: 10.4103/2277-9175.145753
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression with type 2 diabetes and relevant factors

Abstract: Background:Based on the high prevalence of diabetes and depression in Rasht, we conducted a study to evaluate the prevalence of depression in type 2 diabetic patients, and its association with glycemic control, chronic complications, and some clinical and paraclinical parameters in this northern state of Iran.Materials and Methods:Beck depression inventory was used for evaluating depression on 90 type 2 diabetics and 90 healthy controls selected. Information on demographic and clinical and paraclinical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…[ 9 ] In an Iranian study, depression was not correlated with a duration of diabetes and glycemic control. [ 10 ] In the present study, an association between depressive symptoms and either higher HbA1c levels or longer duration of T2DM in males was noted. Blood glucose is known to affect mood, and inversely depression has been suggested to be a possible cause of inadequate metabolic control in T2DM patients.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…[ 9 ] In an Iranian study, depression was not correlated with a duration of diabetes and glycemic control. [ 10 ] In the present study, an association between depressive symptoms and either higher HbA1c levels or longer duration of T2DM in males was noted. Blood glucose is known to affect mood, and inversely depression has been suggested to be a possible cause of inadequate metabolic control in T2DM patients.…”
Section: Discussionsupporting
confidence: 54%
“…[ 7 8 ] However, other studies reported conflicting results claiming a negative relationship between depression and glycemic control, DM duration, or DM complications. [ 9 10 ] It is suspected that the relationships between depression and T2DM-related factors may vary based on the background of the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that prolonged hyperglycemia causes injuries to the retinal vasculature that are not reversed even upon subsequent sustained glycemic control; such impairments may play pivotal roles in “metabolic memory”, rendering patients more susceptible to the complications of diabetes17181920. Last but not least, DM individuals diagnosed between 31–45 years of age are usually under high-level psychological pressure212223. Such stress may explain why DR is more likely in patients in whom diabetes develops at an age of 31–45 years.…”
Section: Discussionmentioning
confidence: 99%
“…Factors related to depression are complex. Among them, prevalence of chronic disease is one of the major factors related to depression (Dejean, Giacomini, Vanstone, & Brundisini, 2013; Huang et al, 2010; Kalantari, Jafarinezhad, & Zohrevand, 2014; Liu, Xu, Hall, Wu, & Zhang, 2016; Wimmelmann, Lund, Hansen, Dela, & Mortensen, 2016; Yang et al, 2016). The relationship between physical health and mental health has been demonstrated in previous studies (Barcelos-Ferreira, Izbicki, Steffens, & Bottino, 2010; Christensen et al, 2016; Kohler, van Boxtel, Jolles, & Verhey, 2011; Mezuk, Edwards, Lohman, Choi, & Lapane, 2012; Riahi et al, 2016; Tsai, Liu, Tsai, & Chung, 2012).…”
Section: Introductionmentioning
confidence: 99%